Number Systems and Data Communication - Elahi, Ata; Arjeski, Trevor (ARM Assembly Language with Hardware Experiments, 2015)
In order to understand network technology it is important to know how information is represented for transmission from one computer to another. Information can be transferred between computers in one of two ways: an analog signal or a digital signal.
Citation Key Alias: lens.org/038-175-763-396-415
Keywords: Analog Signal; Binary Number; Digital Signal; Number System; Transmission Method; dept.csc